Value education and character in textbook of PAI and Character on junior high school year 2017 (analysis content, implementation and strategy) - Awalina Maftukhah (Prodi PGMI IAIN Salatiga, 2017)
The aim of this research is to know the content value and character in textbook of Islamic Religious Education and Character on Junior High School. The implementation and character in SMP Negeri 1 Salatiga, SMP Islam Al Azhar 18 Salatiga and SMP Muhammadiyah Salatiga and the teacher’s strategy of character implementation in the school. This research uses a qualitative approach with a focus on values educationand characters in the handbook Islamic Religious Education. Data were analyzed by content analysis. The validity of research data is by using triangulation techniques with theory. This research also uses observative method, interview and documentation method. Based on this research, can be conclude that the content in textbook of Islamic education and character in Junior High School have 18 point and character. There are some strategy that used by teacher in SMP Negeri 1 Salatiga, SMP Islam Al Azhar 18 Salatiga and SMP Muhammadiyah Salatiga such as integrating in learning. Moreover, it’s also doing by self development in school activity, prayer dhuha, Ikrar and PPK.